Geographic Information System Mapping Potential of E-Market in Pandemic Period - Elda Anzeli Hasibuan; Surya Darma; Nurbaiti Nurbaiti (Penerbit Jurnal Indonesia, 2022)
Changes in people's mindsets in obtaining accurate information are influenced by the rapid advancement of information technology. Currently, one of the most widespread applications of technology is in the field of mapping. Mapping technology is widely used to simplify important tasks. The most widely used mapping technology today is geographic information systems. Geographic Information System (GIS) is a mapping technology trend in the form of computerized information systems designed to work with spatial references. In the current pandemic period, buying and selling products offered are difficult to carry out due to restrictions on social interaction between communities, making it difficult for SMEs to sell their products. The development of information technology, especially the internet, can certainly be used as a medium to overcome these problems. The existence of a website-based information system is intended to support marketing, especially in providing detailed product and price information to consumers. The presence of the COVID-19 pandemic has changed the world with unprecedented challenges and has had a huge impact on daily human activities, resulting in a worsening of the global economy. The COVID-19 pandemic is currently entering its second year, requiring daily activities to be carried out from home. The emergence of the COVID-19 pandemic has also caused business owners to feel a very real decline. In such conditions, a web-based communicative information system is needed, from which it is hoped that problem solving, especially the provision of information about the superior products of SMEs, is needed.